Design elements, form & space : a graphic style manual for understanding structure and design - Puhalla, Dennis M. (Rockport Publishers, 2011)
This is the first volume of the Design Elements series each focusing on a core element of the designer's toolbox. Created with the design student in mind, the series offers a comprehensive reference for understanding and effective application of the core building blocks for designers. Volumes will break down the rules and elements related to each specific subject and outline how and when to apply effective usage and when it's OK to break the rules. Both text book and design reference, this is a library which every designer needs. It promises a solid understanding and usage rules for the core elements of design and providing application-oriented inspiration as a crucial teaching tool